Systematic exploration of WO3/TiO2 heterojunction phase space for applications in photoelectrochemical water splitting - Pinto,F; Wilson,A; Moss,B; Kafizas,A (The Journal of Physical Chemistry C: Energy Conversion and Storage, Optical and Electronic Devices, Interfaces, Nanomaterials, and Hard Matter, 2022)
Recent work has shown that heterojunction photoelectrodes can achieve synergistically higher water splitting activity than their parent materials. To optimize the performance in such layered systems, it is necessary to develop new methods capable of assessing heterojunction phase space. Herein, we explore WO3/TiO2 heterojunction phase space as a model system. Using chemical vapor deposition, 71 unique photoanodes were grown (15 single-layer; 56 heterojunctions). The materials were physically characterized using X-ray diffraction, Raman spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy analysis, and ultraviolet–visible transmission spectroscopy. Various key performance indicators were measured. Within this WO3/TiO2 heterojunction phase space, the onset potentials ranged from ∼0.45 to ∼0.81 VRHE; the incident-photon-to-current efficiencies at 350, 375, and 400 nm ranged from ∼0.6 to ∼50.9, ∼0.1 to ∼30.0, and ∼0 to ∼15.6%, respectively; and the theoretical solar photocurrents ranged from ∼0.01 to ∼0.94 mA cm–2. Contour plots allowed us to identify regions of heterojunction phase space with high activity and establish trends. We identified an electronic barrier to charge transfer between the heterojunction layers that required a sufficiently high applied potential (≥1.0 VRHE) to be surpassed for synergetic improvements in activity to be observed. We recommend that the methods developed herein, for assessing the performance of sample libraries of heterojunction photoelectrodes, be used alongside combinatorial synthesis methods and high-throughput photoelectrochemical measurements to optimize promising heterojunction systems more rigorously and rapidly.